A study on the effect of biostimulant application on yield and quality of tomato under long-lasting water stress conditions - Cristina Patanè; Alessandra Pellegrino; Alessandro Saita; Silvio Calcagno; Salvatore L. Cosentino; Alessio Scandurra; Valeria Cafaro (Heliyon)
Recently, the use of plant-derived biostimulants has been suggested as a sustainable way to improve the nutritional quality of tomato and mitigate the effects of environmental stresses. In this regard, a two-year experiment was conducted in open field on four cultivars of tomato (two commercial tomatoes and two local landraces of long shelf-life tomato), to assess the crop response, in terms of fruit yield and quality traits, to the foliar application of two plant-derived biostimulants based on protein hydrolysates (PH), under opposite water regimes (no irrigation and full irrigation), in a semi-arid environment of South Italy. Tomato plants in field were sprayed with a solution containing one of the two biostimulants approximately every 15 days. Full irrigation significantly promoted plant productivity, leading to yields the 22 % and 57 % higher than those produced under no irrigation. Biostimulants significantly promoted plant productivity (+57 % and +39 %, respectively under no and full irrigation, on the average of the two biostimulants), although in the first year only. Overall, fruit quality was better in fruits produced in plants exposed to prolonged soil water deficit. Biostimulants, across cultivars and water regimes, had no effect or even declined fruit quality in terms of total solids (TS), soluble solids (SS), titratable acidity (TA), reducing sugars (RS). The antioxidants were higher in fruits produced under prolonged soil water deficit. Except in the two commercial tomatoes, lycopene content was greater under full irrigation. Overall, the effects of biostimulants on the antioxidants were rather inconsistent. Significant interactions among the three experimental factors on fruit quality traits suggest that the application of biostimulant should be modulated according to water regime and cultivar, involving specific open-field experiments. Interesting correlations (positive or negative) among all the examined traits were described in the current study. A PCA analysis was conducted to reduce the dimensionality of dataset considering the large number of variables in combination. PCA analysis allowed to distribute cultivars and treatments in four distinct groups, according to quality traits. Fluctuating results between the two years of experiment indicated that the tomato response to the application of biostimulants is strictly season-dependent. Future multi-sites and multi-year research are needed to fine-tune the use of biostimulants and, ultimately, make the crop more economically and environmentally convenient than the cultivation of untreated plants.